Il significato di perfezione in santa Teresa d’Avila: Una prospettiva psicologica - Guarinelli, Stefano (La Scuola Cattolica, 2025)
The objective of this writing is to seek in which ways e with which results the biographical story of Teresa builds the “grammar” of what will be for her the Christian perfection. The point of contact between the spiritual experience of Teresa and its personality is individualized in the notion of interiority, here used in a psychological-descriptive sense and brought back, through the contribution of different authors, to the psychological category of the Itself. From here, the text proceeds following a double articulation. In a first step are reformulated the characteristics of the interiority, understood as processing representative and imagination of the Itself, and it is here analyzed the experiential and evolutionary characteristics. From here, in a second step, is reconstructed the interiority of Teresa, resorting to some exemplary areas: the body sense (by developing the relationship lived by Teresa with disease and with physical space); the identity of Itself (highlighting in the biography of Teresa the early presence of narration, who will come to “weave” a deep storyline of identity); the extension of the “me” and the image of “itself” (by tracing the evolution of the theme of the honra in the spiritual journey of Teresa). The paper concludes by highlighting the psychological consistency, “objective”, of the relationship with God and, in the final analysis, the identification of such a texture precisely with the grammar of Christian perfection.